Rancangan Aplikasi Monitoring Santriwan-Santriwati Pondok Pesantren Berbasis Mobile Android - Zeinky Ghossan Azhar; Ade Putra (STMIK Budi Darma, 2022)
This research was conducted to make it easier for parents to get activity information quickly and in real time, plus the lack of data storage on student activities from the cottage. The development of technology is growing rapidly so that everything is completely computerized, so based on this it is necessary to keep up with the latest developments, so that work in the cottage becomes practical and reduces errors due to human error. Activities to monitor what is done by santriwan or santriwati need to be better improved, so that each student can be monitored or monitored for their educational development. Not to mention, sometimes distance is the main obstacle for parents in obtaining information, plus there is often a delay in information from the boarding school in conveying information to parents of students, by using and applying news technology, the cottage can be simpler and faster in conveying information. to parents of students, and parents of students can also participate in supervising their children in terms of obtaining issues related to using student activities, student attendance and violations committed by students. As technology develops, monitoring software for students has started to appear, but parents have also used smartphones a lot, with Android-based software as a student monitoring media that can be accessed by all parents who leave their children in Islamic boarding schools. The results of this study are a system that can be accessed by guardians of students to monitor students while they are in the pesantren